2007
DOI: 10.1677/joe.1.07043
|View full text |Cite
|
Sign up to set email alerts
|

Effect of age and moderate food restriction on insulin sensitivity in Wistar rats: role of adiposity

Abstract: Insulin resistance develops with ageing in humans and rodents. Here, we have studied the evolution of insulin sensitivity with ageing trying to discriminate the role of adiposity from that of ageing in this process. We performed oral glucose tolerance tests and determined overall and tissue-specific glucose utilization under euglycemic-hyperinsulinemic conditions in 3-, 8-, and 24-month-old rats fed ad libitum, and in 8-and 24-month-old rats after 3 months of calorie restriction. Body composition and adipocyte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

29
122
3
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 116 publications
(155 citation statements)
references
References 42 publications
29
122
3
1
Order By: Relevance
“…Visceral fat mass was increased both in 12 M and 24 M animals, with a more pronounced effect in the 12 M group. Supporting our data, it has been observed that the decrease of insulin sensitivity until 8 months of age is paralleled by a significant increase in visceral and total fat mass, but between 8 and 24 months of age, insulin sensitivity decreases further without significant changes in percent visceral adiposity (Escrivá et al 2007). In our experimental setting, caffeine significantly decreased visceral fat mass in the 12 M, but not in the 24 M, group.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Visceral fat mass was increased both in 12 M and 24 M animals, with a more pronounced effect in the 12 M group. Supporting our data, it has been observed that the decrease of insulin sensitivity until 8 months of age is paralleled by a significant increase in visceral and total fat mass, but between 8 and 24 months of age, insulin sensitivity decreases further without significant changes in percent visceral adiposity (Escrivá et al 2007). In our experimental setting, caffeine significantly decreased visceral fat mass in the 12 M, but not in the 24 M, group.…”
Section: Discussionsupporting
confidence: 89%
“…In our experimental setting, caffeine significantly decreased visceral fat mass in the 12 M, but not in the 24 M, group. Escrivá and coworkers also showed that in 24-month-old rats, the accumulation of retroperitoneal and total body fat is more significant than visceral fat buildup (Escrivá et al 2007). We may have missed a significant effect of caffeine on adipose tissue in 24 M rats, considering that we did not assess whole body fat.…”
Section: Discussionmentioning
confidence: 99%
“…The decrease in serum concentrations of adiponectin and its gene expression in WAT does not seem to be secondary to a decrease in food intake. On the contrary, dietary energy restriction leads to an increase in adiponectin secretion (Escrivá et al 2007, Martin et al 2007. The inhibitory effect of arthritis on adiponectin can be due to the inflammatory response, since macrophage-derived factors inhibit adipocyte differentiation as well as adiponectin and FAS gene expression in murine and human preadipocytes (Constant et al 2006).…”
Section: Discussionmentioning
confidence: 99%
“…The GH/IGF-I and insulin system are also significantly altered following fasting and DR. However, differences in GH response and also in the degree of reduction in circulating IGF-I, IGFBP-3, insulin and in the increase of IGFBP-1 and insulin-sensitivity are evitable (Bartke and Turyn 2001;Bonkowski et al, 2009;Breese et al, 1991;Buschemeyer et al, 2010;Dunn et al, 1997;Escriva et al, 2007;Frystyk et al, 1999;Heijboer et al, 2005;Lee et al, 2010;Shimokawa et al, 2003;Wang et al, 2006;Zhao et al, 2010). Corticosteroids tend to increase more following fasting compared with DR (Sabatino et al, 1991;Shen et al, 2009); body temperature showed a steeper decrease following fasting compared with DR (Koizumi et al, 1992;Longo and Finch 2003a;Shen et al, 2009).…”
Section: Starvation and Stress Resistancementioning
confidence: 99%